In-office wide-awake hand surgery versus traditional surgery in the operating room: a comparison of clinical outcomes and healthcare costs at an academic institution. Issue 5 (September 2019) - Rabinowitz, Justin; Kelly, Thomas; Peterson, Ann; Angermeier, Eric; Kokko, Kyle
Abstract : Background: Our study compared clinical outcomes and healthcare costs of A1 pulley release performed wide-awake in an office setting to A1 pulley release performed in an operating room with monitored anesthesia care (MAC) at a United States academic institution. Methods: A retrospective chart review was performed on consecutive patients who underwent single-digit A1 pulley release wide-awake in an office setting or in an ambulatory surgical center with MAC. Clinical outcomes were assessed using the modified Disabilities Arm Shoulder and Hand (DASH) scores and a telephone questionnaire. Hospital financial records were reviewed for all patients and the summation of professional fee, anesthesiology fee, and hospital fee was calculated to determine healthcare cost. Financial comparisons were stratified by insurance carriers. Results: There were 76 patients with complete records: 43 wide-awake, 33 traditional. Both groups had significant improvement in postoperative quick DASH scores. When asked about subsequent surgery, 100% of wide-awake patients and 68% of traditional patients reported they would prefer to be wide-awake. Eighty percent of wide-awake patients said the procedure was less painful or comparable to a procedure at the dentist. Eighty-four percent of wide-awake patients said their experience was better than they expected, compared to 23% of traditional patients. The traditional group had significantly higher total healthcare costs ($2148.62 vs. $607.65), a more than 250% increase in healthcare spending. Professional reimbursement was significantly higher in the wide-awake group ($607.65 vs. $298.83). Conclusions: A1 pulley release performed with patients wide-awake in an office setting led to higher patient satisfaction, decreased healthcare spending and higher physician reimbursement than when performed in an operating room with sedation.